Formation of the polar debris disc around 99 Herculis. Issue 1 (13th March 2020) - Smallwood, Jeremy L; Franchini, Alessia; Chen, Cheng; Becerril, Eric; Lubow, Stephen H; Yang, Chao-Chin; Martin, Rebecca G
ABSTRACT: We investigate the formation mechanism for the observed nearly polar aligned (perpendicular to the binary orbital plane) debris ring around the eccentric orbit binary 99 Herculis. An initially inclined non-polar debris ring or disc will not remain flat and will not evolve to a polar configuration, due to the effects of differential nodal precession that alter its flat structure. However, a gas disc with embedded well coupled solids around the eccentric binary may evolve to a polar configuration as a result of pressure forces that maintain the disc flatness and as a result of viscous dissipation that allows the disc to increase its tilt. Once the gas disc disperses, the debris disc is in a polar aligned state in which there is little precession. We use three-dimensional hydrodynamical simulations, linear theory, and particle dynamics to study the evolution of a misaligned circumbinary gas disc and explore the effects of the initial disc tilt, mass, and size. We find that for a wide range of parameter space, the polar alignment time-scale is shorter than the lifetime of the gas disc. Using the observed level of alignment of 3° from polar, we place an upper limit on the mass of the gas disc of about $0.014 \, M_\odot$ at the time of gas dispersal. We conclude that the polar debris disc around 99 Her can be explained as the result of an initially moderately inclined gas disc with embedded solids. Such a disc may provide an environment for the formation of polar planets.